Research on dynamic optimization of grain reserves based on two-way options - Jiang, Qijun; Chen, Caixia (Frontiers in Sustainable Food Systems, 2025)
How to optimize grain reserve management, reduce the cost of grain reserve, improve the efficiency of grain reserve and enhance the comprehensive strength of national grain reserve is a practical problem that the government and society pay close attention to. This paper innovatively proposes a two-way option grain reserve model, constructs a dynamic reserve system composed of government and grain storage enterprises, and uses mathematical modeling and optimization methods to explore the optimal option purchase quantity of the government under the two-way option reserve model, and simulates the sensitivity of government and enterprise decision-making parameters. The research shows that the two-way option contract signed by the government and enterprises can effectively reduce the cost of grain reserve and effectively balance the amount of static reserve and dynamic reserve. Under the condition that the total grain reserve remains unchanged, the relationship between the government's optimal grain static reserve and the government's optimal call option purchase and the call option strike price is determined. Depends on the difference of the sum of put option execution cost and reserve cost; The relationship between the government's optimal grain static reserve and the government's optimal call option purchase and the put option strike price depends on the difference between the sum of the call option execution cost and the reserve cost. The government's put purchase is an increasing function of the put strike price and a decreasing function of the two-way option premium and the possibility of grain utilization. Finally, on the basis of analyzing the potential risks in the process of implementing the two-way option of grain reserve, the paper puts forward countermeasures and suggestions. This study has very important theoretical and practical guiding significance for guiding financial institutions to launch financial products and services reasonably.